The Demand for New Antibiotics: Antimicrobial Peptides, Nanoparticles, and Combinatorial Therapies as Future Strategies in Antibacterial Agent Design - León-Buitimea, Angel; Garza-Cárdenas, Cesar R.; Garza-Cervantes, Javier A.; Lerma-Escalera, Jordy A.; Morones-Ramírez, Jose R. (Frontiers in Microbiology, 2020)
The inappropriate use of antibiotics and an inadequate control of infections have led to the emergence of resistant strains which represent a major threat to public health and the global economy. Therefore, research and development of a new generation of antimicrobials to mitigate the spread of antibiotic resistance has become imperative. Current research and technology developments have promoted the improvement of antimicrobial agents that can selectively interact with a target site (e.g., a gene or a cellular process.) or a specific pathogen. Antimicrobial peptides and metal nanoparticles exemplify a novel approach to treat infectious diseases. Nonetheless, combinatorial treatments have been recently considered as an excellent platform to design and develop the next-generation of antibacterial agents. The combination of different drugs offers many advantages over their use as individual chemical moieties; these include: a reduction in dosage of the individual drugs, fewer side-effects compared to the monotherapy, reduced risk for the development of drug resistance, a better combined response compared to the effect of the individual drugs (synergistic effects), wide-spectrum antibacterial action, and the ability to attack simultaneously multiple target sites, in many occasions leading to an increased antibacterial effect. The selection of the appropriate combinatorial treatment is critical for the successful treatment of infections. Therefore, the design of combinatorial treatments provides a pathway to develop antimicrobial therapeutics with broad-spectrum antibacterial action, bactericidal instead of bacteriostatic mechanisms of action and better efficacy against multidrug-resistant bacteria.